Utilization of Pectin from Okra as Binding Agent in Immediate Release Tablets. (30th November 2021) - Owusu, Frederick W. A.; Boakye-Gyasi, Mariam E.; Entsie, Philomena; Bayor, Marcel T.; Ofori-Kwakye, Kwabena
Abstract : Polymeric materials from plants continue to be of interest to pharmaceutical scientists as potential binders in immediate release tablets due to availability, sustainability, and constant supply to feed local pharmaceutical industries. Paracetamol tablet formulations were utilized in investigating the potential binding characteristics of pectin harnessed from various okra genotypes (PC1-PC5) in Ghana. The pectin yields from the different genotypes ranged from 6.12 to 18.84%w/w. The pH of extracted pectin ranged from 6.39 to 6.92, and it had good swelling indices and a low moisture content. Pectin extracted from all genotypes were evaluated as binders (10, 15, and 20%w/v) and compared to tragacanth BP. All formulated tablets (F1-F18) passed the weight uniformity, drug content, hardness, and friability tests. Based on their crushing strength, tablets prepared with pectin from the various genotypes were relatively harder (P ≤ 0.05 ) than tablets prepared with tragacanth BP. Tablets prepared with pectins as binders at 10%w/v and 15%w/v passed the disintegration and dissolution tests with the exception of PC4 at 15%w/v. Incorporation of pectin from all genotypes (excluding PC5) as a binder at concentrations above 15%w/v (F13, F16, F14, and F15) produced tablets which failed the disintegration test and showed poor dissolution profiles. Thus, pectin from these genotypes can be industrially commodified as binders in immediate release tablets using varying concentrations.